Implementasi Sistem Informasi Manajemen Berbasis ICT Dalam Meningkatkan Layanan Akademik Di MA Al Amiriyyah Tegalsari Banyuwangi Tahun Pembelajaran 2018/2019 - Munawir, Munawir; Aziz, Abdul; Afifah, Fiki Nur (Jurnal Manajemen Pendidikan Islam Darussalam, 2019)
The purpose of this study is to find out: 1). ICT-based management information system implementation, 2). the benefits of ICT-based management information systems. and 3). supporting and inhibiting factors in the implementation of a SIM. This study uses a qualitative data analysis with flow methods including 1). Data Reduction, 2). Data Presentation, and 3). Conclusion. The results of this study can be concluded as follows: 1). Implementation of Management Information Systems includes Data input, data handling, and Output processes; 2). Benefits of ICT-based SIM: Student guardians can find out the presence of vulnerable students through the fingerprint system via the SMS gateway. 3)) Supporting factors include: completeness of supporting tools, support from student guardians and cohesiveness of the stakeholders, and Enthusiastic students; and (b). Inhibiting factors: the absence of supporting tools to the guardian and the lack of liking for the tool and students are late in fingerprint